Null mutation analysis of an afsA-family gene, barX, that is involved in biosynthesis of the γ-butyrolactone autoregulator in Streptomyces virginiae - Yong Jik Lee (2018)
Virginiae butanolide (VB) is a γ-butyrolactone autoregulator that triggers production of the streptogramin antibiotic virginiamycin in Streptomyces virginiae. Our previous studies suggested that the barX gene, an afsA-family gene, is likely to participate in the regulatory pathway for the production of VB, rather than in the biosynthetic pathway of VB itself, in contrast to the function of other afsA-family genes. Mutation analysis now shows that BarX at least plays an enzymic role in the VB biosynthetic pathway. Heterologous expression of the afsA gene from Streptomyces griseus into the barX mutant partially restored the deficiency of virginiamycin production, suggesting that afsA-family genes have a common ability to synthesize the γ-butyrolactone autoregulators. Taken together with previous works relating to the function of an afsA-family gene, these results support the idea that streptomycetes have two biosynthetic pathways for the γ-butyrolactone autoregulators. © 2010 SGM.